Integrated Reporting and COVID-19: A Conceptual Reference Disclosure Index for Future Pandemics - Denhere, Varaidzo; Moloi, Tankiso (International Journal of Management and Sustainability, 2022)
The COVID-19 pandemic struck the global community in December 2019 in China and by the beginning of 2020, it had spread to many other countries. The pandemic affected people’s lives and most business sectors. Its impact on business organizations warranted disclosure in the integrated reports for information to investors and other stakeholders. In the absence of a known pandemic disclosure framework, some researchers developed a COVID-19 pandemic reporting framework based on the pre-existing integrated reporting framework, literature from medical, scientific and pharmaceutical field journals, newspapers, and specialized websites as well as interviews of various professional investors in 2020 to guide firms in disclosing COVID-19 issues. This framework has not yet been contrasted by researchers to date. With challenges known to exist in trying to determine the extent of the pandemic disclosure, the objective of this study is to develop a conceptual reference disclosure index for future pandemics using the COVID-19 pandemic as a baseline. The pandemic was severe in 2020 but started to abate in 2021 due to the development of vaccines. COVID-19 information was used to develop the proposed index, and it is anticipated that the proposed index will also be useful for future pandemics. The proposed index should be instrumental in determining the extent of the pandemic disclosure by companies, information that is crucial for investors and all stakeholders for decision making. As there is also paucity in literature on COVID-19 because it is a new experience, this study will contribute to the body of literature in this field.